(untitled) (Construction Economics and Building, 2012)
2nd Edition C Eastman, P Teicholtz, R Sacks and K Liston ISBN: 978-0-470-54137-1 (Hardcover) 648 pages, 2011, AUD 105.00; NZD 120.00, USD 85.00, GBP57.50, EUR 68.00 E-book version ISBN: 978-1-1180-2169-9 544 pages 2011 AUD 84.99 / NZD 99.99, USD69.99, GBP 47.99, EUR 54.99